Formation of Bromate in Pet Bottle Water - Sharif, Haifa (2014)
A Master of Science thesis in Civil Engineering by Haifa Sharif entitled, "Formation of Bromate in Pet Bottle Water," submitted in January 2014. Thesis advisors are Dr. Maruf Mortula and Dr. Serter Atabay. Available are both soft and hard copies of the thesis.